2019
DOI: 10.1177/0361198119854087
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Gender, Mobility, and Personal Safety: South Africa Moving Forward

Abstract: Transport users make mode choices based on a variety of factors. These factors are economic or service driven, based on individual roles, habits, and interests, as well as age, life cycle stage, and gender. Analysis reflects different mobility patterns for males and females relating to care activities. Literature suggests that experiences of harassment have a significant effect on user choices. This study examines how South African data compares with international studies. Mode use and trip purposes, distances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 20 publications
1
14
0
1
Order By: Relevance
“…A particular issue with the vulnerability of pedestrians and public transport users is the added vulnerability experienced by female road users. Further to the increasing recognition and prioritization of women within Global health and development agendas such as within the UN SDG and UHC Agendas [14,16], there is also a growing body of research that in recent years highlight the experiences of vulnerability by females in the road traffic environment as well as their added risk to RTCIs [26][27][28]. In many African countries, females are reported to experience relatively greater risk exposure than men from walking and public transport, with these differences being more pronounced in rural areas [1,29,30].…”
Section: Plos Onementioning
confidence: 99%
“…A particular issue with the vulnerability of pedestrians and public transport users is the added vulnerability experienced by female road users. Further to the increasing recognition and prioritization of women within Global health and development agendas such as within the UN SDG and UHC Agendas [14,16], there is also a growing body of research that in recent years highlight the experiences of vulnerability by females in the road traffic environment as well as their added risk to RTCIs [26][27][28]. In many African countries, females are reported to experience relatively greater risk exposure than men from walking and public transport, with these differences being more pronounced in rural areas [1,29,30].…”
Section: Plos Onementioning
confidence: 99%
“…The ability to negotiate these boundaries, however, occurs differentially on the basis of gender. This research highlights the need to reduce risk of harassment and sexual violence faced by girls and women in Namibia and other SSA contexts (Amoako-Sakyi, 2017; Memela and Maharaj, 2018; Peters, 2000; Porter et al, 2017; Vanderschuren et al, 2019; Tanzarn, 2017; Uteng, 2012). This may occur through a combination of increased securitization of public space, law enforcement, education and behavioural change campaigns aimed at removing the differentiated risks women and girls experience in their mobility.…”
Section: Discussionmentioning
confidence: 91%
“…Trains are considered the least safe, hence, the nding that women prefer other modes of transport. A questionnaire amongst train passengers in Cape Town revealed that, while males only experience pickpocketing (83%) and muggings (17%), females are exposed to pickpocketing (37%) and muggings (47%), as well as verbal (10%) and sexual (6%) harassment (Vanderschuren et al, 2019).…”
Section: Womenmentioning
confidence: 99%
“…Slightly more females (24.5% overall) than males (23.5% overall) use public transport. Females favour bus and MiniBus Taxi (MBT) over the train (Vanderschuren et al, 2019). Furthermore, more women (31% versus 27%) travel to work, while males make more business trips (25% versus only 4%).…”
Section: Womenmentioning
confidence: 99%
See 1 more Smart Citation